LINGUISTIC LANDSCAPE IN A MULTILINGUAL CONTEXT: A CASE OF KENYAN UNIVERSITIES - Muriungi, Stella Wangari; Mudogo, Benard Angatia (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
The linguistic landscape of a place constitutes a clear representation of its language ideology, culture, users’ identity and language practice. These are depicted in verbal language used in public signs including business names, street signs, advertisements and graffiti. The aim of this paper is to examine the language distribution, purpose and authorship of public signage in the multilingual context in Kenyan universities. The paper also examines the students’ attitudes towards the public signs in the sampled institutions. A sample of 185 photos taken from notices, advertisements, building names and posters are analyzed. The analysis reveals that English is the most dominant language used in Universities for both top-down and bottom-up signs, with 77% prevalence. This is attributed to the acceptance of English as a global language and presence of international students and lecturers. A high incidence of informative signs is also noted at 42% of all signage linked with the academic nature of the paper context. The findings also reveal that Kiswahili as an African language with Bantu and Arabic roots is barely utilized in public signs despite its official status. This has implications on language policy and its implementation as it indicates a mismatch between policy and practice.